1979
DOI: 10.1136/sti.55.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus hominis antibodies among children and young adults in Ibadan.

Abstract: SUMMARY A total of 422 sera collected from children and young adults living in Ibadan, Nigeria, has been examined for the presence of antibodies to type 1 and type 2 herpesvirus hominis. Type 1 antibodies were rapidly acquired from the age of 1 year onwards, reflecting the relatively poor living standards and the overcrowded accommodation among the population studied. Type 2 antibodies were acquired between the ages of 3 and 5 years. It is suggested that non-venereal spread of the virus must be responsible; pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…It has been shown that neutralising antibodies to herpes simplex virus type 2 are often acquired in childhood in one African city. 20 Meheus has proposed guidelines for the treatment of genital ulcers in African clinics without laboratory facilities.2' We have confirmed his view that cotrimoxazole two tablets twice daily for one week, combined with saline washes, is an effective regimen for the treatment of chancroid; this is reflected in our in vitro findings, all isolates of H ducreyi being found to be sensitive to trimethoprim (Wall RA, unpublished observation). In view of the high proportion of genital ulcers that is due to chancroid, we have recommended that the optimum treatment for this condition in Gambian health centres should be cotrimoxazole and saline washes, as above, combined…”
Section: Discussionsupporting
confidence: 73%
“…It has been shown that neutralising antibodies to herpes simplex virus type 2 are often acquired in childhood in one African city. 20 Meheus has proposed guidelines for the treatment of genital ulcers in African clinics without laboratory facilities.2' We have confirmed his view that cotrimoxazole two tablets twice daily for one week, combined with saline washes, is an effective regimen for the treatment of chancroid; this is reflected in our in vitro findings, all isolates of H ducreyi being found to be sensitive to trimethoprim (Wall RA, unpublished observation). In view of the high proportion of genital ulcers that is due to chancroid, we have recommended that the optimum treatment for this condition in Gambian health centres should be cotrimoxazole and saline washes, as above, combined…”
Section: Discussionsupporting
confidence: 73%
“…This agrees with previous reports on the effects of the first episode HSV-2 infection on obstetric outcome. [3][4][5][6][7] Contrary to this finding, another previous prospective study in USA reported no significant increase in the negative outcomes of pregnancy among "incident HSV-2 infection" participants, relative to other cohorts. [2] The reason for this difference in research finding may be due to the fact that in advanced countries of the world like USA, there is better health facilities, that ensures better management of pregnant women than in third world countries; this helps reduce the morbidity and mortality associated with all forms of infections, including HSV in advanced countries of the world.…”
Section: Discussionmentioning
confidence: 83%
“…[13] Furthermore, our finding of significant association of incident HSV-2 infection with increased chance of occurrence of LBW deliveries, preterm deliveries, stillbirths, and spontaneous abortions is in agreement with previous reports from USA. [3][4][5][6][7] To our knowledge, this is the first study on the effects of HSV-2 infection on outcome of pregnancy in Nigeria. Consequent on paucity of study reports assessing the burden of HSV-2 infection in pregnancy in Nigeria and Africa, [13] it is difficult to effect comparisons or assess trends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neisseria gonorrhoeae-After incubation at 37°C in 5% carbon dioxide for 48 hours, isolates were confirmed as N gonorrhoeae by colonial appearance, Gram stain, and oxidase test. Chiamydia trachomatis-Specimens were inoculated by centrifugation (2500 x g at 33°C for 1 hour) on to McCoy cells, which were subsequently treated with cycloheximide 2 mg/l in minimum essential medium containing glucose and 10% fetal calf serum, as described by Ripa and Mardh.…”
Section: Identification Of Pathogensmentioning
confidence: 99%